Analisis puisi hafiz ibrahim dalam perspektif naratologi poststrukturalisme - Nadhiyah, Aini Rohtul (Maliki Interdisciplinary Journal, 2025)
This article discusses the application of poststructuralism theory in analyzing the poem Al-Ummah by Hafiz Ibrahim, one of the important figures of modern Arabic literature. Poststructuralism, as a response to structuralism, rejects the idea that the meaning of a text is fixed and objective, and emphasizes the role of the reader in creating meaning through interpretation. The approaches used in this study include poststructuralist narratology and genetic structuralism. The analysis of the poem shows that the narrative in this work has an open structure, with meaning relative and dependent on the reader's perspective. Through narratological theory, the poem Al-Ummah is seen as a call for the revival of the Egyptian nation rich in symbolism, while also reflecting the struggle against colonialism and social injustice. This study also highlights the elements of intertextuality and the instability of meaning in the poem, which provide room for diverse interpretations according to the social context and the reader's experience. Thus, poststructuralism theory becomes a relevant tool for exploring the depth of meaning in literary texts, enriching understanding of the relationship between the text and the socio-political realities that underlie it.